Alterations in White Matter Fiber Tracts Characterized by Automated Fiber-Tract Quantification and Their Correlations With Cognitive Impairment in Neuromyelitis Optica Spectrum Disorder Patients - Yan, Zichun; Wang, Xiaohua; Zhu, Qiyuan; Shi, Zhuowei; Chen, Xiaoya; Han, Yongliang; Zheng, Qiao; Wei, Yiqiu; Wang, Jingjie; Li, Yongmei (Frontiers in Neuroscience, 2022)
Objectives: To investigate whether patients with neuromyelitis optica spectrum disorder (NMOSD) have tract-specific alterations in the white matter (WM) and the correlations between the alterations and cognitive impairment. Materials and Methods: Forty NMOSD patients and 20 healthy controls (HC) who underwent diffusion tensor imaging (DTI) scans and neuropsychological scale assessments were enrolled. Automated fiber-tract quantification (AFQ) was applied to identify and quantify 100 equally spaced nodes of 18 specific WM fiber tracts for each participant. Then the group comparisons of DTI metrics and correlations between different DTI metrics and neuropsychological scales were performed. Results: Regardless of the entire or pointwise level in WM fiber tracts, NMOSD patients exhibited a decreased fractional anisotropy (FA) in the left inferior fronto-occipital fasciculus (L_IFOF) and widespread increased mean diffusion (MD), axial diffusivity (AD) and radial diffusivity (RD), especially for the thalamic radiation (TR), corticospinal tract (CST), IFOF, inferior longitudinal fasciculus (ILF) and superior longitudinal fasciculus (SLF) (P < 0.05, FDR correction), and the pointwise analyses performed more sensitive. Furthermore, the negative correlations among MD, AD, RD and symbol digit modalities test (SDMT) scores in the left TR (L_TR) were found in NMOSD. Conclusion: NMOSD patients exhibited the specific nodes of WM fiber tracts damage, which can enhance our understanding of WM microstructural abnormalities in NMOSD. In addition, the altered DTI metrics were correlated with cognitive impairment, which can be used as imaging markers for early identification of NMOSD cognitive impairment.